ANALISIS HUKUM TERHADAP PERAN PEMERINTAH DAERAH DALAM PENGADAAN TANAH BAGI PEMBANGUNAN - Safiulloh Safiulloh; Aris Setyanto Pramono (Res Justitia : Jurnal Ilmu Hukum, 2022)
Land is a gift of God Almighty for the people, the nation and the State of Indonesia, which must be cultivated, utilized, and used for the greatest prosperity of the people. This article examines the land procurement oriented to the creation of legal certainty of land procurement for local government. Methods Research used normative research methods with statutory approach and analytical or conceptual approach. The results of research indicate that local government has the right and authority to arange and manage its own regional government affairs according to the principles of regional autonomy, especially in terms of land acquisition for the implementation of development for the public interest. However, the authority given to each local goverment, the application must be in synergy with the central government program. If the existence of local government cannot be separated from the central government